Status of the Blackstripe (Fundulus notatus) and Blackspotted (F. olivaceus) Topminnows in the Ozark uplands of Central Missouri - Nathaniel Steffensmeier; Naznin Sultana Remex; Robert Hrabik; David D. Duvernell (Southeastern Fishes Council Proceedings, 2020)
The topminnow species Fundulus notatus and F. olivaceus have broadly overlapping geographic distributions that extend throughout much of the central and southern United States. In the northern portion of their respective ranges, in Missouri, the regional distributions of the two species coincide largely with recognized ecoregions. In the unglaciated southern half of Missouri, F. olivaceus is distributed throughout Ozark upland habitats while F. notatus is abundant in marginal large river and prairie habitats along the Ozark borders. An exception to this partitioning is the historical report of abundant F. notatus in the Bourbeuse and upper Meramec River drainages within the Ozark uplands ecoregion. We conducted an extensive survey of the Bourbeuse and Dry Fork Meramec Rivers to determine topminnow species composition in these systems. Our surveys found abundant F. olivaceus populations throughout these drainages and failed to uncover any F. notatus individuals. A review of museum accessions from the 1940s and 1960s confirms the historical presence of F. notatus in these river drainages, suggesting that a significant shift in topminnow species abundance has occurred in the past half century.
Keywords: ecoregion; species abundance; hybridization; species replacement